2020
DOI: 10.1186/s13045-020-01005-x
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing: new technologies and applications in cancer research

Abstract: Over the past few decades, RNA sequencing has significantly progressed, becoming a paramount approach for transcriptome profiling. The revolution from bulk RNA sequencing to single-molecular, single-cell and spatial transcriptome approaches has enabled increasingly accurate, individual cell resolution incorporated with spatial information. Cancer, a major malignant and heterogeneous lethal disease, remains an enormous challenge in medical research and clinical treatment. As a vital tool, RNA sequencing has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
187
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 332 publications
(219 citation statements)
references
References 208 publications
(187 reference statements)
0
187
0
Order By: Relevance
“…Moreover, we have summarized the most important single-cell sequencing technologies and platforms in Table 1 [ 25 ].…”
Section: Emerging Single-cell Sequencing Technologiesmentioning
confidence: 99%
“…Moreover, we have summarized the most important single-cell sequencing technologies and platforms in Table 1 [ 25 ].…”
Section: Emerging Single-cell Sequencing Technologiesmentioning
confidence: 99%
“…Recent years, transcriptomics research has shown good application prospects in helping researchers deepen their understanding of disease mechanisms and efficiently explore biomarkers (6)(7)(8). Several COPD studies (9)(10)(11) have identified hundreds of biomarkers via differentially analysis based on gene expression profiles from public databases.…”
Section: Introductionmentioning
confidence: 99%
“…High-throughput RNA sequencing (RNA-Seq) is a highly sensitive methodology used to comprehensively evaluate functional mechanisms and molecular heterogeneity through global gene expression analysis 26,27,28,29 . Because of the high sensitivity of the technology, growing technological applications in research, and decreasing costs, RNA-Seq has become an excellent method of evaluating cellular transcriptomes and functionality at a given point in time.…”
Section: Introductionmentioning
confidence: 99%